Sawtone: A universal framework for phonetic similarity and alignment across languages and scripts - Kamali, Omar (Lingua Posnaniensis, 2026)
Processing text across different scripts presents significant hurdles in natural language processing, especially when dealing with non-standardized orthographies and informal writing systems common in low-resource languages. To address this, we introduce Sawtone, an integrated framework designed to enable consistent cross-script phonetic alignment and text normalization. At its heart is an architecture built for interoperability, combining a unified phonological feature space rooted in linguistic principles with modular, language-specific adapters. This structure allows for robust mapping and comparison between any pair of scripts. Crucially, it enables diverse adapters—developed using different methods or data—to work together cohesively for cross-language tasks. The framework readily supports alloglottographic text and is designed to function with minimal resource requirements. We demonstrate its practicality through implementations for transliteration, cross-script sequence alignment, and text normalization, further illustrated by a case study on preprocessing Moroccan Arabic data for Large Language Model (LLM) training. Initial results are encouraging: transliteration reached an 88% BLEU score, phonetic-based text sequence alignment achieved 87-95% accuracy across various language and script pairs, and text normalization significantly reduced variations in spelling. Sawtone offers a structured, interoperable foundation for advancing phonetic-aware NLP across linguistic boundaries.